First-attempt success rate of video laryngoscopy in small infants (VISI): a multicentre, randomised controlled trial. Issue 10266 (12th December 2020) - Garcia-Marcinkiewicz, Annery G; Kovatsis, Pete G; Hunyady, Agnes I; Olomu, Patrick N; Zhang, Bingqing; Sathyamoorthy, Madhankumar; Gonzalez, Adolfo; Kanmanthreddy, Siri; Gálvez, Jorge A; Franz, Amber M; Peyton, James; Park, Raymond; et al.
Summary: Background: Orotracheal intubation of infants using direct laryngoscopy can be challenging. We aimed to investigate whether video laryngoscopy with a standard blade done by anaesthesia clinicians improves the first-attempt success rate of orotracheal intubation and reduces the risk of complications when compared with direct laryngoscopy. We hypothesised that the first-attempt success rate would be higher with video laryngoscopy than with direct laryngoscopy. Methods: In this multicentre, parallel group, randomised controlled trial, we recruited infants without difficult airways abnormalities requiring orotracheal intubation in operating theatres at four quaternary children's hospitals in the USA and one in Australia. We randomly assigned patients (1:1) to video laryngoscopy or direct laryngoscopy using random permuted blocks of size 2, 4, and 6, and stratified by site and clinician role. Guardians were masked to group assignment. The primary outcome was the proportion of infants with a successful first attempt at orotracheal intubation. Analysis (modified intention-to-treat [mITT] and per-protocol) used a generalised estimating equation model to account for clustering of patients treated by the same clinician and institution, and adjusted for gestational age, American Society of Anesthesiologists physical status, weight, clinician role, and institution. The trial is registered at ClinicalTrials.gov, NCT03396432. Findings: Between June 4, 2018, and Aug 19, 2019, 564 infants were randomly assigned: 282 (50%) to video laryngoscopy and 282 (50%) to direct laryngoscopy. The mean age of infants was 5·5 months (SD 3·3). 274 infants in the video laryngoscopy group and 278 infants in the direct laryngoscopy group were included in the mITT analysis. In the video laryngoscopy group, 254 (93%) infants were successfully intubated on the first attempt compared with 244 (88%) in the direct laryngoscopy group (adjusted absolute risk difference 5·5% [95% CI 0·7 to 10·3]; p=0·024). Severe complications occurred in four (2%) infants in the video laryngoscopy group compared with 15 (5%) in the direct laryngoscopy group (–3·7% [–6·5 to –0·9]; p=0·0087). Fewer oesophageal intubations occurred in the video laryngoscopy group (n=1 [<1%]) compared with in the direct laryngoscopy group (n=7 [3%]; –2·3 [–4·3 to –0·3]; p=0·028). Interpretation: Among anaesthetised infants, using video laryngoscopy with a standard blade improves the first-attempt success rate and reduces complications. Funding: Anaesthesia Patient Safety Foundation, Society for Airway Management, and Karl Storz Endoscopy.